2021
DOI: 10.3389/fonc.2021.650355
|View full text |Cite
|
Sign up to set email alerts
|

SLC1A4: A Powerful Prognostic Marker and Promising Therapeutic Target for HCC

Abstract: SLC1A4, a Na-dependent neutral amino acid transporter, was considered to participate in the various pathobiological process, including tumorigenesis. However, the correlation between SLC1A4 and Hepatocellular Carcinoma (HCC) remains unclear. In our study, integrative bioinformatics and functional profiling were performed to reveal the prognosis and potential function of SLC1A4 in HCC. The results showed that the mRNA and protein levels of SLC1A4 were elevated in HCC, and it was a powerful independent prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Our work revealed the ability of the index in predicting the tendency of liver cirrhosis to worsen. This model revealed a close association between HCC and liver failure state by Child-Pugh class classification progression compared with other HCC prognostic markers ( 25 ).…”
Section: Discussionmentioning
confidence: 83%
“…Our work revealed the ability of the index in predicting the tendency of liver cirrhosis to worsen. This model revealed a close association between HCC and liver failure state by Child-Pugh class classification progression compared with other HCC prognostic markers ( 25 ).…”
Section: Discussionmentioning
confidence: 83%
“… 49 In Hepatocellular Carcinoma (HCC), the mRNA and protein expression of SLC1A4 were upregulated, and that could be a novel prognostic marker and promising immunotherapeutic targets of HCC. 9 White et al, demonstrated that SLC1A4 and SLC1A5 might be regulated by androgen receptor (AR), Myc and mechanistic target of rapamycin complex 1 (mTOR) and was high-expressed in prostate cancer. Our results showed the mRNA and protein levels of SLC1A4 were also significantly elevated in LUAD, and were associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 8 The latest study reported that SLC1A4 is upregulated in HCC and involved in various carcinogenesis-associated signaling pathways and processes. 9 Previous studies have shown that SLC1A5 is found to be overexpressed in multiple tumors, including breast cancer, 10 endometrial carcinoma, 11 esophageal cancer, 12 prostate cancer, 13 gastric cancer. 14 In addition, SLC1A5 regulates glutamine uptake cancer growth and tumor development in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, prognostic analysis suggested that higher PTGS2 expression may be associated with poor OS in OV, but the results of different studies were somewhat conflicting ( Steffensen et al, 2007 ). Moreover, SLC1A4, PCK2 and XBP1 were upregulated by 2-fold in erastin-treated HT-1080 cells ( Dixon et al, 2014 ) and could be used as powerful prognostic markers in hepatobiliary cancer ( Liu et al, 2020 ; Peng et al, 2021 ; Wang et al, 2022 ). As the key genes of ferroptosis, SLC3A2, MT1G and ACSL3 have also been widely explored in multiple FRG prognostic models.…”
Section: Discussionmentioning
confidence: 99%